Konseling Kelompok dengan Teknik Cognitive Restructuring dalam Meningkatkan Motivasi Belajar Siswa Slow Learner - Mutmainah, Mutmainah (Bulletin of Counseling and Psychotherapy, 2020)
The slow learner in this study is a condition in which children experience slowness in their cognitive abilities and are below the average normal child so he needs more time to understand or master the subject matter. The purpose of this study was to determine the effectiveness of cognitive restructuring techniques to increase students' slow learner learning motivation, cognitive restructuring techniques to replace negative thoughts and interpretations with positive action thoughts so as not to get used to and become aware of their thought processes. This type of research uses Quasi Experiments with pre-test and post-test designs to compare the experimental group and the control group. Research subjects are slow learner students who have low motivation levels with a total of 14 students. The results of the experimental group measurements showed that the post-test score was higher than the pre-test score. Besides that, the Wilcoxon signed Rank Test test shows that the Sig. <0.05 so that Ho is rejected and Ha is accepted, meaning that there are significant differences in the level of slow learner student learning motivation before and after treatment is given. This shows that group counseling with cognitive restructuring techniques is effective in increasing slow learner students' learning motivation.